PERAN GURU PENDIDIKAN AGAMA ISLAM DAN ORANG TUA DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN PESERTA DIDIK - Rindiani; Mutia Rezky Sari; Sri Irfadianti; Musakkir Ahmad; Tri Ayu Kurnia; Maria Ulviani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Limited Qur’anic reading proficiency can hinder students’ participation in Islamic Religious Education. This article examines the roles of teachers and parents and proposes a collaborative model to improve students’ reading skills. A qualitative narrative review was conducted using nine peer-reviewed articles published between 2021 and 2026. The findings show that teachers support improvement through assessment, differentiated instruction, modeling, guided practice, motivation, habituation, and evaluation. Parents contribute through supervision, emotional support, learning facilities, religious routines, role modeling, and additional guidance. Effective improvement requires regular practice, shared indicators, communication, and follow-up. The main barriers include differences in initial ability, limited time, low confidence, uneven parental competence, and inconsistent home practice. The proposed model includes mapping, intervention, monitoring, and follow-up.